The Continued Impact of Institutional Racism of African American Professional in Corporate America; the Need for Intra-racial Mentoring - Reginald C. Jackson (Adult Education Research Conference, 2014)
This qualitative case study explored the continued impact of institutional racism on African American men in corporate America, their survival techniques when racist incidents occurred and the role that mentoring played throughout their careers. The study also delved into the role of mentoring: both formal and informal and more importantly, the need for intra-racial mentoring.